HUBUNGAN LITERASI DIGITAL, SIKAP MAHASISWA DAN PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) - Sulistiyanto, Figo Ferry; Maria Magdalena; Fikri Hasan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the effects of digital literacy and students' attitudes on the utilization of Artificial Intelligence (AI) for academic communication among students of the Communication Science Study Program at Universitas Merdeka Madiun. A quantitative survey approach was employed, involving 100 respondents selected through purposive sampling. Data were collected using an online questionnaire and analyzed through multiple linear regression with the aid of SPSS software. The findings indicate that digital literacy has a positive and statistically significant effect on AI utilization (t = 3.421; p < 0.05). Students' attitudes also demonstrated a positive and statistically significant effect on AI utilization (t = 3.278, p < 0.05). Furthermore, the simultaneous test revealed that digital literacy and students' attitudes jointly had a significant effect on AI utilization (F = 28.022, p < 0.001). The coefficient of determination (R² = 0.366) further indicated that these two variables explained 36.6% of the variance in AI utilization, while the remaining 63.4% was attributable to factors not included in the regression model.